Assessing and Prioritizing Perceived Service Quality in Healthcare Settings in Nepal: A Multi-Criteria Decision Analysis Using Analytical Hierarchy Process (AHP) - Karki, Ashtha (NCC Journal, 2024)
This study uses the Analytical Hierarchy Process (AHP) to compare and assess different private healthcare facilities in Nepal according to perceived service quality. For methodology, first, the criteria for the study were established and rated. Then sensitivity analysis was carried out to evaluate the decision using AHP to rank healthcare according to the characteristics of service quality and the relative positions. The data were collected from eleven hospitals in Kathmandu, Nepal. SERVQUAL dimensions were used in order to comprehend the Perceived Service Quality. The analytical procedure was carried out using Expert Choice software. The study shows that Private Teaching Hospitals have the highest Perceived Service Quality among patients, followed by Public Teaching Hospitals and that patients value tangibility over other service aspects. The study provides insights into the characteristics of service quality in Nepalese hospitals. The findings help healthcare managers to understand the factors that patients consider important to improve service quality.